COMPARATIVE RISK OF ENDOPHTHALMITIS AFTER INTRAVITREAL INJECTION WITH BEVACIZUMAB, AFLIBERCEPT, AND RANIBIZUMAB. Issue 10 (October 2019) - Bavinger, J. Clay; Yu, Yinxi; VanderBeek, Brian L.
Abstract : Purpose: To determine whether sterile preloading of anti–vascular endothelial growth factor agents reduces the risk of postintravitreal injection endophthalmitis. Methods: This is a retrospective cohort study using medical claims data from a large, national US insurer. Cohorts were created using intravitreal injections of anti–vascular endothelial growth factor injections from 2005 to 2016. For inclusion, patients had to have at least 6 months of data before the injection and were excluded for any previous diagnosis of endophthalmitis, multiple injected drugs on the day of injection, or intraocular surgery within 15 days of the injection or between an injection and a diagnosis of endophthalmitis. The primary outcome was the odds of endophthalmitis after an intravitreal injection. Results: A total of 706, 725 bevacizumab, 210, 849 ranibizumab, and 177, 731 aflibercept injections were given to 130, 327 patients. Multivariate analysis showed that ranibizumab and aflibercept together had an increased odds of endophthalmitis (odds ratio = 1.29, 95% confidence interval: 1.04–1.59, P = 0.02) compared with bevacizumab. Individually, ranibizumab (odds ratio = 1.25, 95% confidence interval: 0.97–1.61, P = 0.08) and aflibercept (odds ratio = 1.34, 95% confidence interval: 0.99–1.81, P = 0.06) each had higher odds of endophthalmitis, but neither result met significance. Also, when compared with male patients, female patients had a higher odds of getting endophthalmitis (odds ratio: 1.30, 95% confidence interval: 1.05–1.61, P = 0.02). Conclusion: The odds of endophthalmitis with aflibercept and ranibizumab combined were higher compared with the sterilely preloaded bevacizumab, arguing for a safety advantage of sterile preloading of anti–vascular endothelial growth factor injections. Abstract : Supplemental Digital Content is Available in the Text.Sterile prepackaging of anti–vascular endothelial growth factor agents into syringes reduces the risk of postinjection endophthalmitis. Women may also be at higher risk for postinjection endophthalmitis compared with men.